Implementation Of Contraception in the Activities Of Children - Nasution, Ade Saputra; Jayanti, Resty; Avianty, Ichayuen; Ekawati, Rindang; Suhenda, Dadang (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
The use of contraceptives in couples of childbearing ages will have an impact on births, the more children are born, the more costs will be incurred to support children and will have an impact on children's health. Growth and development are two events that are different, but interrelated and difficult to separate. The Family Development Program for Toddlers and Children is one of the efforts to foster and increase family planning participation for families of toddlers in supporting the realization of a happy and prosperous small family. This study aims to analyze the effect of family participation in childcare and development and BKB in West Java Province. This type of research is an analytic survey with a cross-sectional research design. Respondents are parents or families who have children under five and preschool in the BKB group and taken by purposive sampling of as many as 2,803 and bivariate analysis using the Chi-Square test. The result variable number of ideal children <0.05 means there is a relationship with the physical growth of toddlers, while the variables of the use of contraceptives and mother's education> 0.05 means there is no relationship with the physical growth of toddlers. The use of contraceptives can indirectly affect the physical growth of toddlers because the use of contraceptives will minimize unwanted births and focus more on the growth and development of children who have been born.